Cyclooxygenase-2 and prostaglandin F2α in syrian hamster leydig cells : Inhibitory role on luteinizing hormone/human chorionic gonadotropin-stimulated testosterone production - Frungieri, Mónica B. (2006)
We have previously found that cyclooxygenase-2 (COX-2), a key enzyme in the biosynthesis of prostaglandins (PGs), is present in the testicular interstitial cells of infertile men, whereas it is absent in human testes with no evident morphological changes or abnormalities. To find an animal model for further investigating COX-2 and its role in testicular steroidogenesis, we screened testes from adult species ranging from mice to monkeys. By using immunohistochemical assays, we found COX-2 expression only in Leydig cells of the reproductively active (peripubertal, pubertal, and adult) seasonal breeder Syrian hamster. COX-2 expression in hamster Leydig cells was confirmed by RT-PCR. In contrast, COX-1 expression was not detected in hamster testes. Because COX-2 expression implies PG synthesis, we investigated the effect of various PGs on testosterone production and found that PGF2α stood out because it significantly reduced human chorionic gonadotropin-stimulated testosterone release from isolated hamster Leydig cells in a dose-dependent manner. This mechanism involves a decreased expression of testicular steroidogenic acute regulatory protein and 17β-hydroxysteroid dehydrogenase. Testicular concentration and content of PGF2α in reproductively active hamsters as well as production of PGF2α from isolated hamster Leydig cells were also determined. Moreover, PGF2α receptors were localized in Leydig cells of hamsters and testicular biopsies from patients with Sertoli cell only and germ arrest syndromes. Thus, in this study, we described a COX-2-initiated pathway that via PGF2α production, PGF2α receptors, steroidogenic acute regulatory protein, and 17β-hydroxysteroid dehydrogenase represents a physiological local inhibitory system of human chorionic gonadotropin-stimulated testosterone production in the Syrian hamster testes.